Local Economic Development in Practice: A Comparative Study Between Montreal and Auckland - Lambert, Marie-Renée (Auckland University of Technology, 2010)
The following thesis presents two real‐life experiences of Local Economic Development (LED) and the evolution of these practices from the dynamics in place prior to the establishment of the practice to its current state of affairs. It uncovers the complexities of LED and how practice has been conditioned by its social, cultural, political and economic environment. There are two stories being presented in this thesis: Montreal LED and Auckland LED. The stories are structured into three patterns of development: the history prior to the establishment of LED; a phase of experimentation; and a phase of what could be described as ‘maturity’. It also offers a detailed picture of current practices. These stories were informed by hundreds of documents and a number of practitioner interviews. Montreal’s first pattern tells a story of empowerment for the French population at both a local and a provincial level. At the local level, the first pattern illustrates the empowerment of community groups and the mobilization of civil society especially in French industrial districts. This had a fundamental impact on the current practices of local economic development as these groups had a significant influence in defining a more socio‐economic focus in LED in Montreal. At the provincial level, empowerment meant a government highly involved in economic development and regional development matters. “Taking control of our own destiny” was a very strong slogan in Quebec during this period. The second pattern shows how the provincial government had a major impact on the development of LED practices. Until recently, provincial government directly funded LED organisations and local organisations reported directly to provincial government. They built trusting relationships over time. The local‐provincial relationships helped favour stability in local economic development areas allowing the long term development of expertise. The second pattern also demonstrates how local economic practices in Quebec are based on the interweaving of bottom up and top down initiatives (from the local community and from the provincial government). Montreal’s third pattern shows how municipal agencies today play a more significant role in local economic development practices, and how they are now major players in controlling funding. Current practitioners that were interviewed described how they have adapted to this change and how they have built new relationships. The third pattern also demonstrates why LED practitioners consult metropolitan economic development plans, and how they attempt to contribute to these plans. Practitioners hold the belief that it is important to show their relevance in the new paradigm of metropolitan economic development. Auckland’s first pattern tells a story in the context of national financial regulation and agricultural exporting. It highlights a national government highly focused on external trade in the pursuit of economic development. There was little concern in the development of regions, with subsidies xii dedicated to industries with export potential; these tended to primarily support industries in the agricultural sector. The second pattern reviews the characteristics of the significant reforms that took place in New Zealand with the major deregulation of the financial system, cuts to subsidies, implementation of a “private sector” management philosophy into the public system, the privatisation of public agencies and the sale of public assets. Central government no longer wanted to “interfere” in the economy and decentralised initiatives relating to employment. During this period, the national government did not fully recognise LED as a tool for development. In fact LED initiatives were primarily funded by programmes dedicated to fight unemployment through business development. Local economic development was only brought in through the creativity in the practices of people working at the local level, who managed to direct funding towards broader issues at the local level. LED is still today focused on business development but now includes industrial development as well. Auckland’s third pattern demonstrates how regional development and sustainable development came more recently into the political agenda. It also illustrates how local agencies came to play more significant roles in local economic development practices. Auckland was recognised as an important engine of economic growth by the national government. As the perceived issues in the governance of the metropolitan region were uncovered, the decision to force amalgamation significantly changed the face of Auckland and the practice of local economic development. The final discussion highlights through comparisons of the two metropolitan regions how these historical developments have influenced current practice. The conclusion reflects on the impact of the findings on local economic development theory and practice as well as proposing other areas for further investigation.
Keywords: Local economic development; Governance